Ready for new waves: optimizing SARS-CoV-2 variants monitoring in pooled samples with droplet digital PCR - Pacini, Antonella; Paredes, Franco; Heckel, Sofia; Ibarra, Guadalupe; Petreli, Maria Victoria; Perez, Marilina; Agnella, Yanina; Piskulic, Laura; Allasia, Maria Belen; Caprile, Luis; Colaneri, Alejandro; Sesma, Juliana (Frontiers in Public Health, 2024)
Introduction The declaration of the end of the Public Health Emergency for COVID-19 on May 11th, 2023, has shifted the global focus led by WHO and CDC towards monitoring the evolution of SARS-CoV-2. Augmenting these international endeavors with local initiatives becomes crucial to not only track the emergence of new variants but also to understand their spread. We present a cost-effective digital PCR-based pooled sample testing methodology tailored for early variant surveillance. Methods Using 1200 retrospective SARS-CoV-2 positive samples, either negative or positive for Delta or Omicron, we assessed the sensitivity and specificity of our detection strategy employing commercial TaqMan variant probes in a 1:9 ratio of variant-positive to variant-negative samples. Results The study achieved 100% sensitivity and 99% specificity in 10-sample pools, with an Area Under the Curve (AUC) exceeding 0.998 in ROC curves, using distinct commercial TaqMan variant probes. Discussion The employment of two separate TaqMan probes for both Delta and Omicron establishes dual validation routes, emphasizing the method’s robustness. Although we used known samples to model realistic emergence scenarios of the Delta and Omicron variants, our main objective is to demonstrate the versatility of this strategy to identify future variant appearances. The utilization of two divergent variants and distinct probes for each confirms the method’s independence from specific variants and probes. This flexibility ensures it can be tailored to recognize any subsequent variant emergence, given the availability of its sequence and a specific probe. Consequently, our approach stands as a robust tool for tracking and managing any new variant outbreak, reinforcing our global readiness against possible future SARS-CoV-2 waves.